The First Resurrection Appearance and the Ending of Mark's Gospel - Trompf, G. W. (New Testament studies, 1972)
Early Christian literature leaves us with apparently conflicting traditions about the first appearance of the risen Lord, although these traditions can be reduced to at least two main classes. On the one hand, some writers give Peter pride of place; he heads the list in Paul's ‘official’ παράδοσις of I Corinthians xv, and takes priority in both Luke (xxiv. 34) and the late second-century Gospel of Peter (xiii. 57 – xiv. 60). On the other hand, some connect women with the first appearance; Matthew presents an albeit brief account of Jesus meeting the three women who had visited the tomb (xxviii. 9–10), whilst John (xx. 11–18) and the longer ending of Mark (xvi. 9) single out Mary Magdalene as the special recipient of the first appearance. As appearances of the resurrected kúpios came to acquire importance for the early Church in establishing apostolic authenticity and leadership, it is surprising that this second line of tradition persisted along with the contradictory ‘pro-Petrine’ material. Was it a source of embarrassment for those wishing to give pre-eminence to Peter? The question has usually been evaded because of the common supposition that Matthew was the first to ‘invent’ the tradition of such an appearance to women, so as to overcome ‘the impasse presented by Mark's (empty tomb) story’ before passing on towards the great summation of his Gospel; but it is also possible to affirm that Matthew (who is pro-Petrine enough, cf. xvi. 17–19) made astonishingly little out of this appearance, sparing as his comments are.